REPOSITIONING THE NATION’S ECONOMY THROUGH NONFORMAL EDUCATION: THE ROLE OF THE NIGERIAN YOUTHS IN ENHANCING PRODUCTIVITY - Abba, Mannir (Sokoto Educational Review, 2011)
One o f the strong concerns of the debate among patriotic Nigerians of different shades of opinion is the aspiration for sustained structural transformation and repositioning of the Nation's Economy. This paper examined ways of repositioning the Nation’s Economy and enhancing productivity by empowering Nigerian Youths through Non-formal Education (NFE). Emerging issues in productivity and economic development, productivity and the challenges o funemployment, government institutional interventions in enhancing youths contributions to higher national productivity and economic restructuring and the task of nation-building and productivity improvement through NFE were highlighted in this paper. Finally, the paper recommended that all hands should be on deck to see to the total success of adult and nonformal education programmes for enhancing productivity and repositioning the nation's economy as education for all is the responsibility of all.